Estimating the impacts of a public transit reform on particulate matter concentration levels: the case of Transantiago in Chile - Figueroa, Eugenio; Gómez-Lobo, Andrés; Jorquera, Pablo; Labrín, Felipe (Estudios de Economía, 2013)
Estimating the specific effects of a complete reform of the public transit system of a large city is a difficult task due to the confounding effects that will usually mask the impact of interest. In this study we estimate the impact of the complete reform of the public transport system in Santiago, Chile, named Transantiago, on a specific aspect of interest: particulate matter air pollution levels in the city. Using a regression model with daily panel data from air quality monitoring stations, we conclude that Transantiago reduced the daily average MP10 concentration levels in at least 3.9 ug/m3. This generates health benefits estimated to be close to US 200 million a year in our medium scenario, 12% of which correspond to lower public sector health expenditure. If the data for the first year of operation of the system (when it was not yet in steady-state) are excluded the estimated reduction in MP10 levels is even higher. Other effects of Transantiago, positive as well as negative, would need to be estimated in order to obtain a comprehensive evaluation of the reform.